Investigation on inherent angle ventilation control of residential kitchen range hoods - Zhilin Guo; Huixing Li; Guohui Feng; Kailiang Huang; Tengfei Yu (Energy and Built Environment)
The emission of oil fume particles during kitchen cooking processes constitutes a significant factor that impacts indoor air quality and human health. Range hoods, as indispensable ventilation devices in kitchens, play a crucial role in reducing indoor particle concentrations. This study employs a combined approach of orthogonal experiments and computational fluid dynamics simulations to investigate the exhaust characteristics of inherent-angle-measurement-based range hoods. It analyzes the diffusion patterns of cooking-generated particulate matter under various cooking scenarios, considering factors such as the opening and closing of windows, cooking source velocities, and different airflow rates of the range hood. Based on different airflow organization patterns, a supplementary ventilation system is designed. The rationality and effectiveness of the supplementary ventilation system are analyzed to establish an effective control scheme for reducing particulate matter in various kitchen environments. The simulated research results indicate that particles disperse along the inclined surface of the side-draft range hood, resulting in higher pollutant concentrations in the breathing zone compared to the cooking zone. Increasing the exhaust airflow rate of the range hood enhances particle capture efficiency by 9.8 %. The induced airflow generated by opening windows improves particle capture efficiency by 12.9 %. However, when the velocity of the window-induced airflow exceeds 1.5 m/s, it hampers the promotion of particle capture efficiency. In the case of windows being unconditionally open, implementing a ceiling-mounted supplementary air supply system effectively improves the kitchen's particle concentration, achieving a maximum particle capture efficiency of 97.66 %. When windows can be opened, setting a baffle on the range hood, the simulation results revealed that with a baffle angle of 120° and a length of 0.3 m, the particle concentration capture efficiency in the breathing zone increased by 34.59 %. This achieved the standard limit requirement of 50 µg/m3, thus meeting the indoor air quality requirements.